Qualification and Hierarchy of Communitarian Law by the Portuguese Constitutional Court and the European Community Court of Justice (Revista da Faculdade de Direito, Universidade de São Paulo, 2006)
This article analyzes the relations between Communitarian Law and Portuguese Law from the Constitutional Court decisions. This study is restricted to related aspects of the hierarchy of norms enacted by the European Union and possible inter-relations between Judiciary Power of the Member States and Communitarian Courts (First-Instance Court and European Community Court of Justice).